(untitled) (Economic and Political Thought, 2017)
A reset in the relations between Washington and Bonn resulted from the reorientation in the United States’ foreign policy that took place when President Barack Obama took office. It was assumed that the problems piling up in front of the new administration in connection with international involvement and the economic crisis were global in character and required cooperation with the allies from NATO (with whom the relations were not good) as well as Russia. President Obama hoped for cooperation with Russia, which many observers described as naïve and attributed to his lack of experience. The reset policy soon started to burn out and there was a gradual process of going away from it. It was stopped by the Russian aggression against Ukraine and the annexation of Crimea in March 2014. The influence of the failure of the reset policy in the American-Russian relations on the American-German relations should be analysed in the context of the two states’ policy and hopes they had in connection with their reciprocal relations. Regardless of the disappointment, because of the two states’ role in international relations, bilateral relations are rational and moderate in character. This concerned and also concerns the policy toward Russia.